(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2025)
The rapid evolution of digital technologies has transformed enterprise operations by introducing intelligent automation, decentralized trust mechanisms, advanced cybersecurity frameworks, and cloud-enabled decision intelligence. Modern organizations increasingly rely on Artificial Intelligence (AI) agents to automate business processes, improve operational efficiency, and support data-driven decision-making. Simultaneously, blockchain technology enhances trust by providing transparent, immutable, and decentralized transaction records that strengthen enterprise governance and collaboration. However, the emergence of quantum computing poses significant threats to conventional cryptographic algorithms, necessitating the adoption of quantum-resilient security models capable of safeguarding enterprise data against future computational attacks. Cloud-orchestrated decision intelligence further integrates distributed computing resources, big data analytics, and AI-powered insights to enable real-time strategic decision-making across complex organizational environments. This study explores the integration of intelligent AI agents, blockchain trust models, quantum-resilient security mechanisms, and cloud-orchestrated decision intelligence as a unified framework for secure enterprise transformation. The proposed approach emphasizes secure data sharing, intelligent process automation, adaptive cybersecurity, and scalable cloud infrastructure to improve organizational resilience and digital innovation. The research highlights how these emerging technologies collectively enhance enterprise security, operational transparency, business agility, regulatory compliance, and sustainable digital transformation while addressing challenges related to privacy, interoperability, governance, and implementation complexity